1991
DOI: 10.1149/1.2085688
|View full text |Cite
|
Sign up to set email alerts
|

A Model of Silicon Carbide Chemical Vapor Deposition

Abstract: We present a model describing the interacting gas phase and surface chemistry present during the steady-state chemical vapor deposition (CVD) of silicon carbide (SIC). In this work, we treat the case of steady-state deposition of SiC from silane (Sill4) and propane (C3H8) mixtures in hydrogen carrier gas at one atmosphere pressure. Epitaxial deposition is assumed to occur on a Pre-existing epitaxial silicon carbide crystal. Pyrolysis of Sill4 and C3H8 is modeled by 83 elementary gas-phase reactions. A set of 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
144
1
2

Year Published

1995
1995
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(152 citation statements)
references
References 17 publications
5
144
1
2
Order By: Relevance
“…Process 2a is 49.8 kcal!mol endothermic with a barrier of 71.9 kcal/ 4, respectively. The kinetic energy release distribution (KERD)2 2 for dehydrogenation CH 3 SiH 2 + -SiCH 3 + + H 2 CH 3 SiClH+ -SiCH 3 + + HCl (3) (4) of metastable CH3SiHz + suggests two distinct mechanisms with substantially different kinetic energy releases. 20 This was interpreted by invoking 1,1-dehydrogenation from the silicon atom (large kinetic energy release) and 1,1-dehydrogenation from the carbon atom (narrow kinetic energy release).…”
Section: Introductionmentioning
confidence: 99%
“…Process 2a is 49.8 kcal!mol endothermic with a barrier of 71.9 kcal/ 4, respectively. The kinetic energy release distribution (KERD)2 2 for dehydrogenation CH 3 SiH 2 + -SiCH 3 + + H 2 CH 3 SiClH+ -SiCH 3 + + HCl (3) (4) of metastable CH3SiHz + suggests two distinct mechanisms with substantially different kinetic energy releases. 20 This was interpreted by invoking 1,1-dehydrogenation from the silicon atom (large kinetic energy release) and 1,1-dehydrogenation from the carbon atom (narrow kinetic energy release).…”
Section: Introductionmentioning
confidence: 99%
“…This led us to study the gas-phase kinetics of hydrocarbons presented in the literature. In this study, we selected two models from the literature, one from Allendorf and Kee 41 and the other from de Persis et al 133 , as well as a model compiled by one of the authors. The simulation conditions were kept the same for all three and no depositions were allowed.…”
Section: Chapter 4 Results and Summarymentioning
confidence: 99%
“…Usage of CFD ranges from designing of reactor geometry to process control. CFD studies of SiC CVD were reported in Ref 38,[41][42][43] .…”
Section: Present Status Of Sic-cvd Process Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results indicate that, in the case of a chemically inert heating zone, the major growth species are Si and C 2 H 2 , resulting from the silane and hydrocarbon precursor decomposition, respectively. This corresponds to the SiC CVD case [17], provided formation of organo-silicon compounds can be neglected. When the incoming gas mixture is allowed to interact with the graphite environment of the growth chamber the major growth species are in turn SiC 2 , Si and Si 2 C, silicon acting in this case as a carbon transporting agent [18].…”
Section: Major Growth Speciesmentioning
confidence: 99%